Answer:
![(v2*m2)/(2*v1 - v2) = m1](https://img.qammunity.org/2019/formulas/mathematics/college/glqd3i9r14f7pjzatub7h09fnjbcd6lh2g.png)
Explanation:
multiply both sides of the equation by (m1 + m2). Bring v1 to the numerator.
v2(m1 + m2) = 2m1 * v1 Remove the brackets on the left.
v2*m1 + v2*m2 = 2*m1*v1 Subtract v2 m1 from both sides.
v2*m2 = 2m1*v1 - v2*m1 Use the distributive property to get m1 alone on the right.
v2*m2 = m1(2*v1 - v2) Divide both sides by (2*v1 - v2)
![(v2*m2)/(2*v1 - v2) = m1](https://img.qammunity.org/2019/formulas/mathematics/college/glqd3i9r14f7pjzatub7h09fnjbcd6lh2g.png)